Using an inerter to enhance an active-passive-combined vehicle suspension system. (15th August 2021) - He, Haonan; Li, Yuan; Jiang, Jason Zheng; Burrow, Steve; Neild, Simon; Conn, Andrew
Highlights: A novel active-passive-combined control approach integrated with an inerter is proposed, to improve the trade-off between the dynamic performance and control requirements. Automotive suspension design is taken as an example, with analytical expressions for the performance indicators obtained using the Lyapunov equations. Pareto optimality improvement is obtained using a simple inerter-based combined absorber. The optimal passive layout of the combined absorber, consisting of inerter, spring and damper with a pre-determined complexity, is identified, achieving further pareto optimality improvement. Abstract: Performance of a passive vehicle suspension can be improved with the help of an active actuator, however, with potentially problematic control requirements, such as high energy consumption and large actuator forces. To maximize performance benefits without requiring significant control efforts, the passive and active parts need to be designed and work synergistically. In this paper, a novel combined passive and active vibration suppression approach of which the passive part is enhanced by an inerter is proposed for improving the trade-off between dynamic performance and control requirements. Via this approach, the optimal passive configuration consisting of inerter(s), spring(s) and damper(s) with pre-determined numbers and the optimal active control parameter can be identified. The approach is demonstrated using a case study where the combined suspension is designed considering a quarter-car model and a typical active controller (i.e., the skyhook control). It will be shown that, compared with a conventional passive part of a spring-damper, adding an inerter in parallel can significantly improve the pareto optimality between the ride comfort and power (or force) requirements. The improvement is further enhanced by systematically exploring all passive network possibilities with a pre-determined complexity via the structure-immittance technique. This approach is also applicable to the vibration suppression of other engineering structures. Graphical abstract: Image, graphical abstract